Neuroinflammation - the Trojan Horse of Neurodegeneration: Dissecting Regional, Genetic and Therapeutic Modulation of Astrocyte Reactivity in Alzheimer's Disease - Imiolek, Magdalena (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2026)
Neuroinflammation is more widely accepted to play a cardinal role in the onset and progression of neurodegenerative disease. Yet despite extensive evidence, its contribution is still often underestimated, thought to operate more subtly than classical pathological hallmarks. In this thesis, neuroinflammation is conceptualised as a 'Trojan Horse' of neurodegeneration, an insidious process that infiltrates early, amplifies cellular dysfunction and accelerates downstream pathology long before clinical symptoms emerge. To investigate this idea, human iPSC-derived astrocytes were assessed for their response to Alzheimer's disease-relevant stressors and the potential of cannabinoids to modulate these inflammatory pathways was explored. Using human iPSC-derived astrocytes, reproducible models of astrocyte reactivity were established and an idea that regional identity shapes inflammatory behaviour was explored. Cortical (CTX) and ventral midbrain (VM) astrocytes displayed distinct basal profiles and differential sensitivity to IL-1α, TNFα+IL-17A and TNFα+IL 1α+C1q (TIC) stimulation, with region-specific secretion of mediators such as CXCL10, IL-6, RANTES and GM-CSF, as well as a wide array of inflammatory and metabolic genes. This regional divergence suggests that astrocytes from different brain areas contribute to neuroinflammatory landscapes in unique ways. Furthermore, we elucidated that APOE genotype significantly modifies these responses in CTX astrocytes, with APOE4 cells exhibiting heightened inflammatory sensitivity and altered transcriptional signatures. Aβ1-40 and Aβ1-42 oligomers induce species- and dose-dependent changes in viability and cytokine release, highlighting astrocytic vulnerability to Alzheimer's disease-associated stressors. The therapeutic component of this work demonstrates that cannabinoids (CBD, THC and their combination) effectively dampen IL-1α-induced inflammatory signalling in CTX astrocytes. Cannabinoids reduce NFκB nuclear translocation, suppress cytokine and chemokine release and downregulate multiple inflammation-associated genes. Mechanistic interrogation using PPARγ agonist/antagonist and CB1 receptor antagonist reveals that these effects are mediated through coordinated modulation of NFκB-, PPARγ- and CB1-linked pathways. By contrast, the NLRP3 inhibitor MCC950 shows only minimal activity, reflecting limited inflammasome competence in fully-differentiated human astrocytes. Together, these findings provide new insight into the molecular drivers of human astrocyte reactivity, reveal region-, APOE- and Aβ-dependent susceptibilities relevant to neurodegeneration, and identify cannabinoid-responsive pathways with therapeutic promise. This work supports the notion that neuroinflammation, though often underestimated, acts as a Trojan Horse in neurodegenerative disease, quietly shaping pathology from within, and underscores the importance of human iPSC-based models for developing astrocyte-targeted interventions.
APPROVED
Keywords: neuroinflammation; Alzheimer's disease; iPSC; neurodegeneration; astrocytes; Stem cell